A multipropriedade à luz do direito luso-brasileiro - Milena, Felipe Sammarco (2023)
The aim of this research is to broaden a critical view on the legal regime of time-sharing of real estate in the Brazilian jurisdiction, through the comparison with a similar institute in the Lusitanian jurisdiction, named as in rem right of periodic occupation. In both compared dimensions, it is possible to assess significant similarities and differences. One of these differences consists in the legal nature of the referred institutes. In Brazil, multi-ownership consists of a condominium regime in which each of the owners of the same property is entitled to a fraction of time, corresponding to the faculty of use and enjoyment of the entire property. Brazilian time-sharing is, therefore, treated as a type of special condominium, being a current expression of property right. In Portugal, the legislator chose to create the in rem right of periodic occupation, an autonomous and singular in rem right, besides the surface, the usufruct rights, among others. In this field, there is a simultaneous coexistence of the entrepreneur’s property right and the user’s in rem right of periodic occupation. In two countries where tourism is dominant, it is opportune to explore such institutes, in order to enable a better understanding of the different features in which the sharing of the property in time is constituted. Furthermore, the great proximity between Brazil and Portugal in terms of culture and law brings greater value to this work